ANALISIS BREAK EVEN POINT PADA MEBEL REZKY - A. FAZA KHOIRUL WAFA; AHMAD TOMU (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine how much sales in units and rupiah and how much tolerance for sales decline in Rezky Furniture Business. The data collection technique used in this study was interviews. The data analysis instrument used in this study was using the break event point and margin of safety calculation methods. The results of the study showed that Rezky Furniture Business would be at breakeven if it sold 28 units or Rp 24,116,549. For window leaf products, it would breakeven if it sold 67 units or Rp 30,294,323. For door frame products, it would breakeven if it sold 151 units or Rp 45,244,061. For window frame products, it would breakeven if it sold 107 units or Rp 31,995,138. Rezky Furniture Business can determine the tolerance for declining sales of furniture products must be above sales per break-even point, namely for door leaf products 88%, for window leaf products 76%, for door frame products 3%, and for window frame products 44%, from current production